Climate modelling of the potential distribution in South Africa of two Zygogramma species (Coleoptera: Chrysomelidae) released for the biological control of invasive weed Tithonia rotundifolia (Asteraceae: Heliantheae) - Khethani V. Mawela; David O. Simelane; Terence Olckers (BioControl, 2024)
Two Mexican leaf-feeding beetles, Zygogramma piceicollis (Stål) and Zygogramma signatipennis (Stål) (Coleoptera: Chrysomelidae), were released in South Africa for the biological control of the invasive species Tithonia rotundifolia (Mill.) S.E. Blake (Asteraceae: Heliantheae). The aim of this study was to predict the potential of these beetles to establish and spread in South Africa, using MaxEnt climate modelling that incorporated locality data recorded in Mexico between 2008 and 2019 and data from the Global Biodiversity Information Facility. Zygogramma signatipennis displayed a wider distribution than Z. piceicollis in Mexico, with some overlap between the two species. The average receiver operating characteristic curves obtained for Z. piceicollis and Z. signatipennis predicted high mean area under curve values of 0.910 and 0.885, respectively. Jackknife tests revealed that mean annual temperature had the highest gain when used in isolation for Z. piceicollis , compared with minimum precipitation of the driest month for Z. signatipennis . These tests also revealed that the highest and lowest contributing environmental variables for Z. piceicollis and Z. signatipennis were minimum precipitation of the driest month (37.9 and 46.7%) and maximum annual temperature of the warmest month (3.8 and 12.3%), respectively. MaxEnt modelling predicted that at least six of South Africa’s nine provinces provide regions that would support the proliferation of both beetles, with conditions best suited for Z. piceicollis . Despite predictions that both beetles should establish throughout the range of T. rotundifolia in South Africa, their realized establishment has so far been poor. Other factors, besides climate, including release size, site destructions, drought, soil moisture and texture could be constraining establishment.

Impact of biocontrol agents on Lantana camara in an inland area of South Africa - Naweji Katembo; Ed T. F. Witkowski; David O. Simelane; Alan J. Urban; Marcus J. Byrne (BioControl, 2020)

Biological control of Lantana camara in South Africa: targeting a different niche with a root-feeding agent, Longitarsus sp. - David O. Simelane (BioControl, 2005)